2009
DOI: 10.1007/978-3-642-02713-0_43
|View full text |Cite
|
Sign up to set email alerts
|

Groupware Accessibility for Persons with Disabilities

Abstract: The accessibility issues of Groupware applications prevent visually impaired and other persons with disabilities access to these highly graphical interfaces. To address the accessibility issues persons with disabilities have with Groupware, a recent literature review on Groupware accessibility was performed. This paper reviews recent research to identify the accessibility issues; the input devices and output forms utilized to improve accessibility; and, the proposed solutions for Groupware accessibility. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The use of audio allows these participants to access knowledge using an auxiliary source via listening (Schoeberlein and Wang 2009). However, four dyslexic participants found the audio to be distracting.…”
Section: Helps In Pronunciationmentioning
confidence: 99%
“…The use of audio allows these participants to access knowledge using an auxiliary source via listening (Schoeberlein and Wang 2009). However, four dyslexic participants found the audio to be distracting.…”
Section: Helps In Pronunciationmentioning
confidence: 99%
“…When a group of users works on a single task, the productivity and the quality of the work increases and decision making becomes faster and more efficient [13]. This is achieved through a groupware environment that has the functions of collaboration and coordination in it [7]. To achieve a high coordination and collaboration quality, group awareness and the support of coordination are essential.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, individuals can be more productive if they work collaboratively in a group [6]. However, individuals with visual impairments struggle when they interact with such applications [7], as they are not particularly designed for them. Add-ons [8] and interface wrappers [9] have been developed to make applications accessible to them, however, they are still not fully utilizable.…”
Section: Introductionmentioning
confidence: 99%
“…Although ThinkFree proved effective for the proposed tasks, efficiency and availability of resources were more limited than in Google Docs. Schoeberlein et al (Schoeberlein & Yuanqiong, 2009), revising recent literature on groupware accessibility and existing solutions, have highlighted the need for future research. Authors observed that most articles address the needs of a specific category of disabled persons.…”
Section: Related Workmentioning
confidence: 99%